Relations among speech, language, and reading disorders - Pennington, BF; Bishop, DVM (Annual Reviews, 2008)
In this article, we critically review the evidence for overlap among three developmental disorders, namely speech sound disorder (SSD), language impairment (LI), and reading disability (RD), at three levels of analysis: diagnostic, cognitive, and etiological. We find that while overlap exists at all three levels, it varies by comorbidity subtype, and the relations among these three disorders are complex and not fully understood. We evaluate which comorbidity models can be rejected or supported as explanations for why and how these three disorders overlap and what new data are needed to better define their relations.